Entrevue guidée avec Karen Messing - Esther Cloutier; Ana-Maria Seifert; Nicole Vézina (Perspectives Interdisciplinaires sur le Travail et la Santé)
Karen Messing granted us an interview for the magazine’s Défricheurs de PISTES section. In her case, she is a groundbreaker. In fact, throughout her professional life, she has been interested in the specific issues related to the subject of gender in work, and particularly to women’s work and its impacts on their health. She was a professor at the Université du Québec à Montréal, and has just begun her “official” retirement. She has a doctorate in biology and gradually became interested in the subject of the work environment and its effects on people’s health. In the early 1990s, she refined her skills in ergonomics in order to have the necessary work analysis tools. Her research has investigated several professions (orderlies, cleaning workers, cashiers, etc.). Karen Messing has published several important scientific books and articles on this issue. We invite you to get to know her a little better.